Comparison of fecal microbiota and metabolites in diarrheal piglets pre-and post-weaning - Huang, Tao; Dong, Jiangpeng; Zhang, Wenyu; Hu, Zhengyu; Tan, Xuhui; Li, Hao; Sun, Kailing; Zhao, Ayong; Huang, Min (Frontiers in Veterinary Science, 2025)
IntroductionDiarrhea after weaning of piglets is one of the most serious diseases in pig herds, which brings huge economic losses to the pig industry. Diarrhea in piglets after weaning has a significant impact on the composition of gut microbiota, which leads to the disturbance of normal metabolic processes.MethodTo investigate the effects of weaning diarrhea on gut microbiota and its metabolites, 84 samples were collected from 42 piglets pre-weaning and post-weaning, including 17 samples from post-weaning diarrheal piglets. The samples were sequenced for 16S rRNA and untargeted metabolites.ResultsA total of 3,192 ASVs, 20 phyla, and 286 genera were identified. A total of 32 genera were detected by difference analysis between healthy post-weaning piglets and diarrhea post-weaning piglets. It was observed that post-weaning diarrhea led to a reduction in the relative abundance of Bacteroides, UCG-002, Christensenellaceae_R-7_group, Escherichia-Shigella, Pyramidobacter, Lactobacillus and a substantial increase in the relative abundance of Prevotellaceae_NK3B31_group, Muribaculaceae, Prevotella, Holdemanella, Collinsella, Blautia. A total of 360 differential metabolites were detected between healthy and diarrheal weaned piglets. 5-Hydroxyferulic acid methyl ester, D-Saccharic acid 1,4-lactone, 3-Methylhistidine were significantly enriched in post-weaning diarrheal piglets. These differential metabolites were enriched in the Nucleotide metabolism, ABC transporters, Biosynthesis of amino acids, Nicotinate and nicotinamide metabolism, Valine, leucine and isoleucine biosynthesis, Pyrimidine metabolism, Alanine, aspartate and glutamate metabolism, Purine metabolism, Caffeine metabolism, Butanoate metabolism pathways.DiscussionTaken together, this study systematically reveals the dynamic succession and structure of the gut microbiota and metabolites in diarrhea and healthy piglets pre-weaning and post-weaning. Our findings provide a reference for the microbiological and metabolite etiology associated with post-weaning diarrhea.